2019
DOI: 10.3389/fphys.2019.01157
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of IL-1β by Aliskiren Improved Renal AQP2 Expression and Urinary Concentration Defect in Ureteral Obstruction and Release

Abstract: We previously demonstrated that ureteral obstruction is associated with a urinary concentrating defect and reduced expression of renal aquaporins (AQPs), in which the renin–angiotensin system (RAS) may play an important role. The aims of the present study were to examine whether the renin inhibitor aliskiren could prevent the reduction in AQP expression and improve the urinary concentrating capacity in mice with bilateral ureteral obstruction (BUO) and BUO release. BUO was performed for 24 h, and BUO release w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Our recent studies 36 , 37 have revealed an inhibitory role of NLRP3 inflammasome in the regulation of aquaporins in the kidneys. In order to unravel the potential mechanism by which cholesterol may affect the protein expression of AQP2, the protein expression profiles of ASC, an adaptor of NLRP3 inflammasome, were examined in the kidney specimens of patients with or without atorvastatin treatment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our recent studies 36 , 37 have revealed an inhibitory role of NLRP3 inflammasome in the regulation of aquaporins in the kidneys. In order to unravel the potential mechanism by which cholesterol may affect the protein expression of AQP2, the protein expression profiles of ASC, an adaptor of NLRP3 inflammasome, were examined in the kidney specimens of patients with or without atorvastatin treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Next we examined a potential mechanism by which cholesterol may impact the protein expression of AQP2. Our recent studies 36 , 37 have revealed an inhibitory role of NLRP3 inflammasome in the regulation of aquaporins of the kidneys. As expected, the protein expression of ASC monomer, cleaved Caspase-1 (p20) and cleaved IL-1β in the kidneys was found to be upregulated in wild type mice on a HFD; while in nlrp3 -/- mice, the HFD seemed to have failed to induce significant changes in the protein expression of ASC, Caspase-1 (p20) and cleaved IL-1β expression (Figure 3 A and B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunofluorescence staining was performed as described previously. 31 After dewaxing and rehydration, kidney tissue For inner medullary collecting duct 3 (IMCD3) cells, in brief, filters were detached from the holders, and cells were fixed with methanol for 2 minutes at −20℃, and permeabilized with PBS-Triton 0.3% for 25 minutes at room temperature and then vacuum permeabilization buffer. Filters were incubated with the rabbit polyclonal anti-p62 (1:200), anti-LC3B (1:200, 18725-1-AP, Proteintech) and anti-LAMP1 (1:200) antibody or mouse monoclonal anti-ASC (1:50, sc-514414, Santa Cruz Biotechnology) overnight at 4℃.…”
Section: Immunofluorescence Stainingmentioning
confidence: 99%